Penerapan Servant Leadership Model di Sekolah Dasar Negeri (SDN) 007 Pangkalan Kerinci - Amirudin, Amirudin; Nuraini, Putri; Widodo, Widodo; Saputra, Herman; Nurjannah, Siti (UIR Press, 2025)
This study aims to look at the implementation of an effective servant leadership model for primary school principals with a focus on the implementation of the servant leadership model at SDN 007 Pangkalan Kerinci. This model has great significance in efforts to improve the quality of school principals, which will have a positive impact on the quality of basic education. Based on the results of the national principal competency test, it appears that the competency of primary school principals shows the lowest results compared to principals at the junior secondary and senior secondary levels. This research applies the case study method to analyze the behavior of individuals, particularly school principals. The key informant in this study is the principal. The collection method was through interviews, observations, and documentation. Qualitative data analysis was conducted using the Miles dan Huberman model. The implementation of the servant leadership model at SDN 007 Pangkalan Kerinci shows that this approach can create a better educational environment and improved student welfare. Through active involvement of all stakeholders, innovative programs and strong support for new teachers, the principal succeeded in building a collaborative atmosphere that supports student and teacher development.